A Novel Technique of Uterine Manipulation in Laparoscopic Pelvic Oncosurgical Procedures: "The Uterine Hitch Technique". (10th January 2010) - Puntambekar, S. P.; Patil, A. M.; Rayate, N. V.; Puntambekar, S. S.; Sathe, R. M.; Kulkarni, M. A.
Abstract : Aim . To describe a new technique of uterine manipulation in laparoscopic management of pelvic cancers. Material and Methods . We used a novel uterine hitch technique in 23 patients from May 2008 to October 2008. These patients underwent pelvic oncologic surgery including laparoscopic radical hysterectomy (n = 7 ), laparoscopic anterior resection (n = 4 ), laparoscopic abdominoperineal resection (n = 3 ), laparoscopic posterior exenteration (n = 4 ), or laparoscopic anterior exenteration (n = 5 ). The uterus was hitched to the anterior abdominal.wall by either a single suture in the fundus or by sutures through the round ligaments. Results . The uterine hitch technique was successfully accomplished in all procedures. It was performed in less than 5 minutes in all cases. It obviated the need for vaginal manipulation. An extra port for retraction could be avoided. There were no intraoperative complications. Conclusion . A practical, cheap and reproducible method for uterine manipulation, during pelvic oncologic surgery is described. It improves the stability of the uterus and also obviates the need for keeping an additional assistant for vaginal manipulation in any of the procedures.